Controlled unfolding of elastic hinge - Muhammad Faiz Mohd Basir (Nanyang Technological University, 2021)
The main source of power in satellites are from the attached solar panels. Weight limitations mean that these solar panels are thin and intricate. As such, it is important to ensure that there is minimal impact force during deployment to prevent any damages on the solar panels. Polycaprolactone (PCL) polymer possesses damping characteristics that are able to achieve safe deployment of these solar panels. Apart from the damping characteristics, this report will explore the suitability of PCL polymer for the controlled unfolding of hinges attached to such solar panels. Carbon fibre will be laced in the PCL samples to increase its stiffness and also act as a heat source to explore other properties that will be elaborated in the report. Apart from that, different experiments conducted to study the properties of PCL and also the steps taken during the composite sample preparation for experimental testing will be explored. The main objective of this project is to study the suitability and effectiveness of PCL for controlled unfolding of elastic hinges and also the power consumption of the PCL composites.